Suling Dewa Sebagai Identitas Simbolik Masyarakat Sasak Kuto-Kute di Karang Bajo Bayan Lombok Utara - Muhammad Arsyad Nur Kholis; Wahyu Kurnia (Universitas Gadjah Mada, 2021)
This study aims to identify the role of Suling Dewa as a symbolic identity of the Karang Bajo community, North Lombok. The groups living in Bayan have different backgrounds. This phenomenon becomes interesting when among the four community groups in Wet Bayan, only the Karang Bajo people present different symbolic values for the existence of Suling Dewa. This theory used in this study is the theory of Burke and Jan E. Stets which states that identity is formed through symbols and the meaning of symbols as a perception. To see how the ideological reflection the author also refers to Thomson's opinion on ideology and the use of symbolic forms and the attraction between interpretation, self-reflection, and identity criticism. This research identifies that the background predicate as spiritualists in the Karang Bajo community is a fundamental substance that gives birth to a symbolic identity of a supernatural bridge in Suling Dewa.